Conversation Analysis: Turn-Taking Analysis on Boy William Podcast Episode 06 in Collaboration with Cinta Laura - Tyas, Novita Kusumaning; Pratama, Febi Gilang (Allure Journal, 2022)
This study is proposed to analyze conversation analysis especially for turn- taking strategy in a podcast of Boy William especially in the 6th episode, collaboration with Cinta Laura Kiel, one of Indonesian artist. This study used qualitative method with Stenstroom’s framework was used to analyze the turn- taking strategy used in the conversation. The process of analysis consists of four steps; streaming Boy William’s podcast 6th episode with Cinta Laura, making transcription of the conversation, classifying the data and interpreting the data. The result of this study showed that turn- taking strategy appear in the conversation. There were starting up, promoting, interrupting, repeating words, taking over, overlapping, appealing, silent pause and filled pause. The most frequent turn- taking strategy used is promoting strategy. Therefore, this study suggests that conversation analysis is important for understanding the intent of people's speech. In addition, this study can be used as a reflection of both theoretical and practical contributions. In theory, this study supports the theory of conversation analysis in turn- taking strategies. In fact, teachers can use it as a reference for applied linguistics courses.